Morphological, Molecular and Genomic Identification and Characterisation of Monilinia fructicola in Prunus persica from Portugal - Elsa Baltazar; Sara Rodrigues; Aitana Ares; Alexandra Camelo; Inês Brandão; Christophe Espirito Santo; João Trovão; Eva Garcia; Joana Costa (Agronomy, 2023)
In Portugal, the Cova da Beira region is well-known for the production of Prunus spp. and is considered the main peach production area in the country. In the spring of 2021 and 2022, field surveys in peach and nectarine orchards showed symptoms of decline such as cankers, gummosis, dry branches, abortion of flowers, mummified fruits and the partial or total death of some plants. Brown rot is caused by three species of the genus Monilinia, M. fructigena, M. laxa and M. fructicola, the last is an OEPP/EPPO A2 quarantine organism on peach trees. Brown rot disease had previously been described in the Cova da Beira region, however, the recent high mortality and severity of symptoms raised doubts as to the species involved. Symptomatic plant material was collected from thirteen orchards and used for fungal isolation and molecular detection according to the OEPP/EPPO standard. M. fructicola was confirmed morphologically and molecularly in two orchards, and molecularly (duplex real-time PCR) detected in two others. Whole genome sequencing using Oxford Nanopore MinION was also carried out to confirm the identification. Pathogenicity tests were performed on peach, nectarine and sweet cherry fruit according to Koch’s postulates. Based on all the results obtained, we report the first detection of M. fructicola in P. persica in Portugal.